PENGARUH SEKTOR INDUSTRI PENGOLAHAN DAN BANGUNAN TERHADAP KUALITAS UDARA KOTA PEKANBARU - Ahmad Jain; Nursiah Chalid; Eriyati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Economic growth in the manufacturing sector and the building has an influence on the air quality in Pekanbaru. The purpose of this paper is to know how the influence of Manufacturing industry sector and building sector to air quality of Pekanbaru city in 2007 - 2013. The method of data collection is documentation. The method of Data analysis in this research is descriptive analysis. Results from this study showed that the growth in the manufacturing sector have an influence on air quality, but do not have a major impact on air quality damage in Pekanbaru Because the rate of growth in the manufacturing sector tend to decline more than in 2007 - 2013. While the growth of the construction sector has a considerable influence on the damage to air quality, because of the rapid physical development to improve the quality and service of the city of Pekanbaru. Disruption of air quality Pekanbaru also more caused by land and forest fires as well as an increase in the number of motor vehicles. Growth in the manufacturing sector and building in this study was measured using Produk Domestik Regional Bruto (PDRB) based on 2000 constant prices expressed as a percentage and Indeks Standar Pencemaran Udara (ISPU) to measure air quality Pekanbaru . The conclusion of this study is the growth of the construction sector has a strong influence on the air quality of the city of Pekanbaru. Advice can be given in this study are all efforts made to boost economic growth should be in line with efforts to maintain and improve the quality of air in order to create sustainable development in the city of Pekanbaru.Keywords: Manufacturing Industry Sector, Building Sector, and Air Quality